Impact of Slow Stroke Back Massage on Blood Pressure Among Individuals With Primary Hypertension: A Quasi-Experimental Study - Bastian, Wrestina Ari; Nugroho, Setiyo Adi; Wicaksi, Damon (Adult Health Nursing Journal, 2025)
Introduction:  Hypertension is a major global health issue contributing significantly to cardiovascular morbidity and mortality. In Indonesia, the increasing prevalence of hypertension highlights the need for effective, low-cost, non-pharmacological interventions, such as Slow Stroke Back Massage (SSBM), which may offer physiological and psychological benefits.  Objectives:  This study aimed to determine the effect of Slow Stroke Back Massage on reducing systolic and diastolic blood pressure among individuals with primary hypertension.  Methods:  A quasi-experimental study using a non-equivalent control group pretest-posttest design was conducted. Participants aged 40–70 years with primary hypertension were purposively selected and divided into intervention and control groups. The intervention group received SSBM once daily for three consecutive days, while the control group received standard care. Blood pressure measurements were recorded before and after intervention using calibrated digital sphygmomanometers. Data were analyzed using paired and independent t-tests. Results:  The intervention group experienced a significant reduction in both systolic (from 150.2 ± 10.5 mmHg to 137.6 ± 9.8 mmHg) and diastolic (from 95.8 ± 6.2 mmHg to 87.3 ± 5.6 mmHg) blood pressure (p < 0.001). No statistically significant changes were observed in the control group. These results support the efficacy of SSBM as an adjunctive therapy in hypertension management.  Conclusions: SSBM is an effective, low-cost, and non-invasive complementary intervention for lowering blood pressure in patients with primary hypertension. It can be integrated into nursing care practices, especially in primary healthcare settings, to enhance hypertension management outcomes.